Resection of Olfactory Groove Meningiomas Through Unilateral vs. Bilateral Approaches: A Systematic Review and Meta-Analysis - Feng, Austin Y.; Wong, Sandy; Saluja, Sabir; Jin, Michael C.; Thai, Anthony; Pendharkar, Arjun V.; Ho, Allen L.; Reddy, Prasad; Efron, Allen D. (Frontiers in Oncology, 2020)
Introduction: Consensus is limited regarding the optimal transcranial approaches (TCAs) for surgical resection of olfactory groove meningiomas (OGMs). This systematic review and meta-analysis aim to examine operative and peri-operative outcomes of unilateral compared to bilateral TCAs for OGMs. Methods: Electronic databases were searched from inception until December 2019 for studies delineating TCAs for OGM patients. Patient demographics, preoperative symptoms, surgical outcomes and complications were evaluated and analyzed with meta-analysis of proportions. Results: 27 observational case series comparing 554 unilateral versus 451 bilateral TCA patients were eligible for review. Weighted pooled incidence of gross total resection (GTR) is 94.6% (95% CI, 90.7-97.5%; I2 = 59.0%; p = 0.001) for unilateral and 90.9% (95% CI, 85.6-95.4%; I2 = 58.1%; p = 0.003) for bilateral cohorts. Similarly, incidence of OGM recurrence is 2.6% (95% CI, 0.4-6.0%; I2 = 53.1%; p = 0.012) and 4.7% (95% CI, 1.4-9.2%; I2 = 55.3%; p = 0.006) respectively. Differences in oncologic outcomes were not found to be statistically significant (p = 0.21 and 0.35 respectively). Statistically significant differences in complication rates in bilateral vs unilateral TCA cohorts include meningitis (1.0% vs 0.0%; p = 0.022) and mortality (3.2% vs 0.2%; p = 0.007). Conclusions: While both cohorts have similar oncologic outcomes, bilateral TCA patients exhibit higher post-operative complication rates. This may be explained by underlying tumor characteristics necessitating more radical resection but may also indicate increased morbidity with bilateral approaches. However, evidence from more controlled, comparative studies is warranted to further support these findings.